Practical Life : Efforts To Train Independence In Early Children - Nurilla Santi, M.Pd (MultiTech Publisher, 2023)
This research aims to explain Practical life activities in an effort to train early childhood independence through habituation. This type of research is descriptive qualitative which is directed towards narrative studies. The participant in this research was a class teacher at As-Syuhada Kindergarten, Wargo Mulyo Village, Kapuas Kuala District, Kapuas Regency. The results and findings of the research are that there are learning strategies in implementing practical life activities in an effort to train early childhood independence with the following steps: 1) Teachers provide repetitive activities (habituation) to early childhood, 2) Teacher preparation for learning to train children's independence early age, 3) Effective teachers are able to create a cheerful learning atmosphere and attract attention in an effort to train early childhood independence, 4) Creative teachers in an effort to train early childhood independence. However, during the implementation of Practical Life, during break times, children wash their hands before eating, there is a lack of hand washing facilities and infrastructure because only one hand washing facility is used in 2 classes between Kindergarten A and Kindergarten B, so the children - children scramble to wash their hands. Even at that time, the teacher's preparation was still not able to see the situation and provide a quick solution to provide easy facilities such as providing water in another tub so that there was no fighting over it and not directing children to be disciplined in queuing.